2008
DOI: 10.1016/j.catena.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal characteristics of soil particle size distribution under different land-use types on the Loess Plateau, China

Abstract: Soil particle-size distribution (PSD) is one of the most important physical attributes due to its great influence on soil properties related to water movement, productivity, and soil erosion. The multifractal measures were useful tools in characterization of PSD in soils with different taxonomies. Land-use type largely influences PSD in a soil, but information on how this occurs for different land-use types is very limited. In this paper, multifractal Rényi dimension was applied to characterize PSD in soils wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 36 publications
8
132
6
Order By: Relevance
“…In this study, the texture of soil was determined as loose soil [16], for which the ideal BD should be less than 1.60 g¨cm´3 [5]. The comparison of BD after harvest in the six cropping durations showed that all of them had soil with BD lower than the critical value (1.60 g¨cm´3).…”
Section: Soil Physicochemical Indicator Among Cropping Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the texture of soil was determined as loose soil [16], for which the ideal BD should be less than 1.60 g¨cm´3 [5]. The comparison of BD after harvest in the six cropping durations showed that all of them had soil with BD lower than the critical value (1.60 g¨cm´3).…”
Section: Soil Physicochemical Indicator Among Cropping Yearsmentioning
confidence: 99%
“…Schjonning [15] reported that a desirable BD could increase soil water-reserving ability. In this study, the ideal BD was considered to be 1.60 g¨cm´3 [16,17], and all of the six cropping durations had soil with BD lower than this critical value. Therefore, a curve of "more is better" was applied to BD.…”
Section: Soil Quality Index (Sqi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation, determining slope, aspect, etc., is the main feature of topography, which influences spatial distribution of roads and buildings at the local scale; gully line, another feature of topography, changed quickly at the fringe of Dongzhi Yuan and was closely related to the rate of soil erosion (Wang 2007). Thus, coefficient of variation (CV) of elevation (Zhang et al 1999;Gustafson et al 2005;Wang et al 2008) and gully line density (the ratio of gully line length to sample area) in 120 samples were selected as independent variables of topography. Land cover in Dongzhi Yuan is relatively simple, mainly including farmland, forest, shrub, and grassland (Chen et al 2007b), so the percents of areas of these types were directly calculated as independent variables of land cover.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…However, this was by and large ignored in the present work. It would be particularly interesting to find out more about how the authors distinguished between the fractal dimension defined as used in the present study and the fractal dimension used in the classic literature (Brown et al 1996;Hyslip and Vallejo 1997;Posadas et al 2001;Wang et al 2008). …”
mentioning
confidence: 99%